A Refleksi Tartibat Terhadap Fenomena Taraduf Dalam Bahasa Arab: Studi Kitab Fiqh Al-Lughah Wa Asrar Al-'Arabiyyah - Yusril Ihza Elyas; Faisol; Al Anshory, Abdul Muntaqim (Journal of Practice Learning and Educational Development, 2025)
Fiqh Lughah wa Asrar Al-‘Arabiyyah is one of the important works in the development of Arabic linguistics. This book has two main discussions, first is fiqh lughah which discusses the specification of the meaning of Arabic vocabulary and the second is asrar al-‘arabiyyah which discusses the linguistics of the content and rules of the Arabic language. In the first discussion, there are chapters that have several specific categories such as kulliyyat, tartibat, tafshilat, taqsimat and others. This study aims to discuss one type of meaning categorization in the book of Fiqh Lughah wa Asrar Al-‘Arabiyyah that is tartibat and its relevance to the principle of taraduf (synonymy) in Arabic. The study is limited to the categorization of tartibat which includes the condition of human feelings and expressions so that the study can focus on the reflection of tartibat in relation to the form of relativity of taraduf in Arabic. This research method uses a qualitative research approach with reference to the analysis of literature studies. The results of this study are that there are six scopes (sub-categories) of the tartibat categorization in the book of Fiqh Lughah wa Asrar Al-‘arabiyyah which show human feelings and expressions consisting of tartibat al-buka`, tartibat al-dhahak, tartibat aushaf al-bakhil, tartibat al-hubb, tartibat al-ghadhab, and tartibat al-surur. From the six scopes of data, words with close meanings were found, but each shows a different situation specification.